Pengaruh Profitabilitas dan Kebijakan Dividen terhadap Harga Saham dengan Struktur Modal sebagai Variabel Intervening pada Perusahaan yang Terdaftar di IDXHIDIV20 Periode 2021-2024 - Andika Rizky Ekaputra Prabantono; Faridhatun Faidah (Jurnal Studi Manajemen Bisnis, 2026)
This study aims to analyze the effects of profitability and dividend policy on stock prices, with capital structure as an intervening variable, for companies listed in the IDXHIDIV20 index during 2021–2024. This research employs a quantitative approach using panel data from 11 companies, resulting in 44 observations. Profitability is measured by Return on Equity (ROE), dividend policy by Dividend Payout Ratio (DPR), capital structure by Debt-to-Equity Ratio (DER), and stock prices by annual closing prices. The data were analyzed using multiple regression and path analysis. The results indicate that: (1) profitability has a positive and significant effect on stock prices, (2) dividend policy has a significant negative effect on stock prices, (3) profitability has a significant negative effect on capital structure, (4) dividend policy has no significant effect on capital structure, and (5) capital structure has no significant effect on stock prices. Furthermore, capital structure has not been shown to mediate the relationships between profitability and dividend policy, and between profitability and stock prices.